Community Service In Strengthening The Governance Of Occupational Safety And Health Competency Certification Through A Web-Based Information System At PT Batamindo Investment Cakrawala - Hilda Herasmus; Agus Suryadi; Mulyanto (PT. Padang Tekno Corp, 2026)
The Level 2 Working at Height (TKBT) training conducted by PT Batamindo Investment Cakrawala produced 22 certified employees across four divisions. However, post-training recommendations from the HRD unit identified the absence of a periodic monitoring mechanism for certificate validity periods and personal protective equipment usage, while all record keeping remained paper-based and spreadsheet-driven. This condition creates a compliance risk against Minister of Manpower Regulation Number 9 of 2016, as expired certificates may go undetected before employees are assigned to work at height. This community service program aims to strengthen the partner's occupational safety competency certification governance through the design, implementation, and mentoring of a web-based information system. The implementation method consists of six stages: situation analysis, requirements analysis, system design, construction, socialisation and training, and operational mentoring. The system was developed using a three-tier architecture and comprises four core modules: certificate record management, automated validity notification, divisional recapitulation dashboard, and digital document archiving. Program effectiveness was measured using a pre-test and post-test design with a 20-item instrument covering four knowledge domains, analysed using normalized gain. Functional testing was conducted using the black box method, while user acceptance was measured using the System Usability Scale. The results show that participants' average knowledge score increased from 51.4 in the pre-test to 86.4 in the post-test, with a normalized gain of 0.72 categorised as high. Black box testing achieved a 90 percent success rate and the System Usability Scale score reached 82.5, indicating good user acceptance.